La relación entre los niveles de escolaridad y la informalidad laboral. Un análisis para Ecuador durante el año 2022 - Eras Alava, Jorge Alberto (2025)
In Ecuador, 53,5 % of the employed population works in the informal sector, marking the highest percentage since the fourth quarter of 2020. This issue mainly affects sectors such as agriculture, construction, and commerce. This study analyzes the relationship between education level and the probability of working in the informal sector, based on the hypothesis that a higher level of education significantly reduces this probability (examining the conjecture that increasing education levels substantially mitigates this issue). To achieve this, annual data from the 2022 ENEMDU survey was used, which provides national representativeness, is disaggregated by area, and extends to each province in Ecuador. A probit model was employed to examine the relationship between education and informality, along with the Oaxaca-Blinder (1973) methodology to determine the educational gap between sectors. The results show that in rural areas, informality prevails due to the prevalence of unregulated primary-sector jobs, leading to job insecurity. Additionally, an increase in years of schooling significantly reduces the likelihood of working in the informal sector, as informal employment typically requires fewer formal credentials such as certifications or academic degrees. Moreover, an educational gap between sectors was identified, largely attributed to structural labor market inequalities. Finally, it is recommended that relevant authorities implement or enhance social programs to mitigate the effects of labor informality.